Mathematical Problem Solving in E-Learning Based on David Kolb's Learning Style - Putri Endah Wulandari; Akhsanul In'am; Zukhrufurrohmah . (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This qualitative descriptive research aims to describe mathematical problem-solving ability in e-learning in terms of David Kolb’s style study. The research subject was 54 students of Mathematics Education in the sixth semester who took the Vector Analysis course. Data collection techniques used are questionnaires, tests, and interviews. Two students from each learning style were randomly selected. Data obtained from the test results in a description analyzed and described in a narrative based on an indicator of mathematical problem-solving ability. The results showed that the assimilator learning style dominates the other learning styles. The solution of a problem mathematical for a student on the e-learning based on type assimilator learning style can be filled four phases of Polya problem solving maximally. The diverger type can only follow the necessary steps to solve the problems until they execute the strategy. Converger and accommodator types can perform the same four phases of the Polya problem-solving but must be optimized. Further research includes digging up information about learning styles outside of David Kolb and conducting observations and interviews to measure suitability with David Kolb's learning style.Penelitian ini adalah penelitian deskriptif kualitatif yang bertujuan untuk mendeskripsikan kemampuan pemecahan masalah matematis pada e- learning berdasarkan dari gaya belajar David Kolb. Subjek penelitian adalah 54 mahasiswa Pendidikan Matematika semester VI yang menempuh mata kuliah Analisis Vektor. Teknik pengumpulan data yang digunakan ialah angket, tes, dan wawancara. Dua mahasiswa dari setiap gaya belajar dipilih secara acak. Data yang diperoleh dari hasil tes berbentuk uraian dianalisis dan dideskripsikan secara narasi berdasarkan indikator kemampuan pemecahan masalah matematis. Hasil penelitian menunjukkan bahwa tipe gaya belajar assimilator mendominasi tipe gaya belajar lainnya. Pemecahan masalah matematis mahasiswa pada e-learning berdasarkan tipe gaya belajar assimilator dapat memenuhi empat tahapan pemecahan masalah Polya secara maksimal. Mahasiswa dengan tipe gaya belajar diverger hanya mampu memenuhi tahapan pemecahan masalah Polya hingga pada melaksanakan strategi. Mahasiswa dengan tipe gaya belajar converger dan accomodator mampu melaksanakan empat tahapan pemecahan masalah Polya namun belum maksimal karena terdapat indikator yang belum terpenuhi. Penelitian lebih lanjut antara lain menggali informasi mengenai gaya belajar diluar David Kolb, melakukan observasi dan wawancara untuk mengukur kesesuaian dengan gaya belajar David Kolb.